Turkish approach to minority concept evolution of minority concept and competence of Treaty of Lausanne in contemporary times - Yoğun, Mirhan (İstanbul Bilgi Üniversitesi, 2019)
Although there are different views on its emergence, minority concept has always occupied a wide place within the past and today of political life. Since social differences among people all around the world will not disappear in the short run, this situation will continue in the future. Yet, from past to present the meaning attributed to minority concept has been subject to a change process and this situation, naturally, causes changes also in approaches to minority concept and progress in minority rights and protection. Since the Ottoman era, approaches toward minority groups living in Turkey has always been- directly or indirectly- affected by all these changes. Thus, widely-accepted minority concept and ground for minority protection in Turkey have been evolved within this framework. Main aim of this thesis has been the examination of the Treaty of Lausanne -as the main minority protection document of Turkey- in terms of its competency with evolving minority concept and minority protection principles in the world. Within this context, history of minority concept accepted in international level and minority protection principles were given place, after that, the competence of the Treaty of Lausanne with this evolution process has been questioned.

Azınlık kavramı, ortaya çıkışına dair farklı yaklaşımlar olmasına rağmen siyasi hayatın dünü ve bugününde geniş yer kaplamıştır. Sosyal farklılıklar dünyanın her yerinde yakın gelecekte ortadan kalkmayacağından, bu durum gelecekte de devam edecektir. Ancak geçmişten bugüne azınlık kavramına yüklenen anlam tüm diğer kavramlar gibi bir değişim sürecine tabidir ve bu durum azınlık kavramına olan yaklaşım ile birlikte azınlık hakları ve koruması alanında da değişimlere yol açmaktadır. Osmanlı İmparatorluğu’ndan bu yana Türkiye topraklarında yaşayan azınlık gruplarına karşı gelişen yaklaşım da tüm bu değişimlerden direkt veya dolaylı olarak etkilenmiş, günümüzde karşılaşılan azınlık tanımı ve azınlık koruması zemini de bu çerçevede evrilerek bugüne gelmiştir. Bu tezin temel konusu da evrilerek gelişen azınlık kavramı ve azınlık koruma prensiplerine, Türkiye’nin temel azınlık koruma metni olarak kabul edilen Lozan Antlaşması’nın ne derece uyumlu olduğudur. Bu çerçevede uluslararası alanda kabul gören azınlık kavramı ve azınlık koruma prensiplerinin tarihçesine yer verilmiş ve Lozan Antlaşması’nın bu evrilme süreci ile olan benzerlik ve farklılıkları ayrıca günümüz standartlarına göre yeterliliği sorgulanmıştır.